Assessment Of Chemotherapy Outcome And Adverse Event Management Among Solid Cancer Patients Of Penang Hospital - Hassan, Bassam Abdul Rasool (2013)
During this century, cancer has become one of the major problem and diseases which has caused predominant death and will even surpass heart diseases. Both cancer diseases and chemotherapy have many hazardous side effects which could also affect the quality of life (QOL) of cancer patients. Thus this study was performed to detect the main risk factors associated with nausea and vomiting, anemia, thrombocytopenia and hypercalcemia and to evaluate effectiveness of respective treatment guidelines. In addition QOL of breast cancer patients with nausea and vomiting was also evaluated. Prospective and retrospective studies were conducted on solid cancer patients admitted to Penang, Hospital. Data were collected by using direct person-toperson interview for the prospective part (nausea and vomiting) and by using specific data sheet for the retrospective part (anemia, thrombocytopenia and hypercalcemia). The required data were collected from patients’ files kept in the oncology clinic and the record office of the hospital.